PENGHAPUSAN PENDAFTARAN MEREK BERDASARKAN GUGATAN PIHAK KETIGA - Mardianto, Agus (Faculty of Law, Universitas Jenderal Soedirman, 2010)
The right of a trademark is an exclusive right granted by government. A registered trademark can be cancelled from the General List of Trademark. Cancellation of registration of a trademark can be claimed by a third party through a dispute to a Commercial Court based on article 61 paragraph (2) letter b of Trademark Law 2001. This research is aimed at studying the use of article 61 paragraph (2) letter b of Trademark Law 2001 as the base of dispute for cancelation of the registration of a trademark by a third party, and studying the legal consequences of a trademark cancelation. A qualitative juridicial normative method with descriptive analyses approaches was used to analyze secondary data derived from documents of decisions of Commercial Court of Central Jakarta Number 06/Merek/205/PN.Niaga.JKT.PST and documents of decisions of Supreme Court of the Republic of Indonesia Number 031K/N/HaKI2005. The result of the research showed that the application of article 61 paragraph (2) letter b of Trademark Law 2001 for the base of decision of the judges of Commercial Court of Central Jakarta was inappropritate. In judging at the use of a trademark, the judges only looked at the inconsistency of writtting styles or fonts or colours, but not taking into considerations of the purpose and intention of the parties that claimed the dispute. Cancelation of regitration of a trademark based on the dispute of a third party automatically resulted in the termination of legal protection of the related trademark.Keywords: trademark, cancelation of a trademark, third party, good intention, Commercial Court